The Efficacy of Watermelon (Citrullus lanatus) Rind Extract in Healing Burns in Balb/C Male Mice - Megahandayani, Siti Wahyuputri; Mahastari, Nur Lailiyah Yoan; Lasmono, Roisa Zakia Zahra; Jannah, Siti Nur; Affifah, Virmin Rahma; Siddiq, Hadi Barru Hakam Fajar (MPI (Media Pharmaceutica Indonesiana), 2023)
Burns are skin tissue damage that occurs as a result of direct contact with a heat source. One of the natural treatments for burns is watermelon (Citrullus lanatus) rind. Watermelon rind contains citrulline, an alkaloid that plays a role in wound healing. This study aims to explore the potential of watermelon rind to become extract gel as a burn remover in male Balb/C strain mice. This research method is a true experiment that begins with the preparation of watermelon rind extract by maceration with ethanol. Furthermore, the polyphenol, flavonoid, saponin, and alkaloid content of the extract was identified through the phytochemical screening. The next stage was the preparation of a gel with three variations of extract concentrations, namely 25%, 50%, and 75% w/v. The gels were characterized by organoleptic, pH, and spreadability. The final stage tested the gel’s activity as a burn wound healing in male Balb/C strain mice. The results showed that the extract contained saponins, polyphenols, flavonoids, and alkaloids. The spreadability test results of the gel showed that all gels met the requirements. All gels had activity against burns in male Balb/C strain mice. Thus, watermelon rind extract can be used as a medicine for burns.